2013 Curriculum Report Application Development at SMK DIAN Indonesia: Pengembangan Aplikasi Raport Kurikulum 2013 Di SMK DIAN Indonesia - Asy’Ari, Mochammad Hasyim; Untari, Rahmania Sri; Hasanah, Fitria Nur (Universitas Muhammadiyah Sidoarjo, 2018)
In SMA Dian Indonesia the report card data entry process is still constrained by the complexity of the application flow that is used. Each subject teacher gives a grade to the homeroom teacher to be processed into a report card. This made it difficult for the homeroom teacher to process the data provided by the subject teacher so that the process of processing report cards was hampered.